Cutting carbon and nitrogen footprints of maize production by optimizing nitrogen management under different irrigation methods - Di, Yunfei; Gao, Yu; Yang, Haibo; Yan, Dong; Tang, Yuzhe; Zhang, Weijian; Hu, Yuncai; Li, Fei (Frontiers in Plant Science, 2024)
Analyzing the effects of nitrogen (N) fertilizer application and water management on the carbon (C) and N footprints is vital to maize production systems. Thus, this study conducted field experiments from 2019-2020 involving flood and drip irrigated maize production systems in Northwest China to analyze N and C footprints (NF and CF, respectively) based on the life cycle assessment (LCA). The N fertilizer treatments studied included no N fertilizer application (Control), optimized N management (OM), optimized N management incorporated with urease inhibitor (OMI, UI), and farmer practice (FP). The maize grain yields under flood irrigation afforded by OMI (12.3 t ha-1) and FP treatments (13.4 t ha-1) were significantly higher than that of OM treatment (11.0 t ha-1). But maize grain yields of the OM (12.1 t ha-1), OMI (12.5 t ha-1), and FP treatments (12.5 t ha-1) showed no significant difference under drip irrigation although less N was applied to OM and OMI. The OMI treatment had better environmental effects than the OM treatment under both flood and drip irrigation. Applying N fertilizer with UI increased N use efficiency (NUE) and reduced N losses under flood irrigation. The reactive N (Nr) losses, greenhouse gas (GHG) emissions, NF, and CF of OMI treatment were 43.9%, 45.3%, 35.7%, and 37.4% lower under flood irrigation and 43.3%, 37.1%, 43.2%, and 37.1% lower under drip irrigation compared to the FP treatment. The Nr losses, GHG emissions, NF, and CF of drip irrigation were lower than those of flood irrigation. According to the analysis of driven indicators, the N leaching, electricity for irrigation, and NH3 volatilization were the most important contributors to the NF; the fertilizer, electricity for irrigation, and N2O emissions were the dominant factors controlling the CF. The environmental impact of the OMI treatment was less than that of the OM and FP treatments. Therefore, integrating better N management practices and efficient irrigation methods can significantly reduce environmental impacts while maintaining yields in maize cultivation.